2017
DOI: 10.1088/1757-899x/261/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Recommendation System to Match College Events and Groups to Students

Abstract: With the recent increase in data online, discovering meaningful opportunities can be time-consuming and complicated for many individuals. To overcome this data overload challenge, we present a novel text-content-based recommender system as a valuable tool to predict user interests. To that end, we develop a specific procedure to create user models and item feature-vectors, where items are described in free text. The user model is generated by soliciting from a user a few keywords and expanding those keywords i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…The definition of meta-knowledge is extracting knowledge from feature representation and also we can define it as perfect feature extraction and pre-selected knowledge from unstructured data [39], [40], [41]. The meta-knowledge or perfect feature extraction allows the deep study of feature for the purpose of more precise knowledge.…”
Section: A Meta-knowledgementioning
confidence: 99%
“…The definition of meta-knowledge is extracting knowledge from feature representation and also we can define it as perfect feature extraction and pre-selected knowledge from unstructured data [39], [40], [41]. The meta-knowledge or perfect feature extraction allows the deep study of feature for the purpose of more precise knowledge.…”
Section: A Meta-knowledgementioning
confidence: 99%
“…Obtaining generic keywords which may have a greater chance of being indexed in BabelNet is a good solution. Qazanfari et al [26] showed that using lemmas improved the precision and accuracy of their recommendation system. That is why lemmatization is included in both search approaches (i.e., exact and further).…”
Section: Introductionmentioning
confidence: 99%
“…Medir la Similitud Semántica Textual (SST) entre oraciones o conceptos es una tarea fundamental en varias aplicaciones del Procesamiento del Lenguaje Natural (PLN), por ejemplo, en Sistemas de Recomendación (SR). Un SR es una subclase de filtrado de información que coleccionan información sobre las preferencias de los usuarios para un conjunto de elementos como películas, canciones, libros, aplicaciones, sitios web, entre otros [1], una vez filtrada la información guían a los usuarios para descubrir productos o servicios en una forma personalizada [2,3]. Otra aplicación de la tarea de SST es para ofrecer explicaciones verbales a partir de un par de oraciones [4], lo cual puede ser aplicado en sistemas de tutorado inteligente [5], en recuperación de información para medir la similitud entre la consulta y textos almacenados en una colección de documentos [6], entre otras aplicaciones.…”
Section: Introductionunclassified